Organization and Activities of State Administration in Biomedical Assisted Insemination - Radošević, Ratko (Zbornik radova Pravnog fakulteta u Novom Sadu, 2016)
The state administration activities are practiced in different areas of social life, including the field of biomedicine. In this paper, the author explains which activities of the state administration are practiced in the field of biomedical assisted insemination and by which bodies of the state administration. Given the fact that the activities of the state administration have a different nature, the attention is paid only to authoritative activities in individual situations.